Soap of Mendoza: Contribution to the Study of Trans-Andean Trade (1697-1870) [Jabón de Mendoza: Aporte Para el Estudio del Comercio Trasandino (1697-1870)] - Lacoste, P (Verlag Vervuert, 2019)
In the framework of the trans-Andean trade of the seventeenth, eighteenth and nineteenth centuries, a relevant role fitted Mendoza s soap. This was a typical product, famous for its quality and highly demanded by foreign markets: it was exported regularly to Chile and Peru, and it was sold in California during the gold rush. from this case study, we seek to make a contribution to the understanding of intra-Latin American regional trade in a historical period in which the attention of the mainstream of the academy has focused on exchanges with markets of the North Atlantic. from unpublished original archival documentation, this article provides evidence to understand the high quality of this product, which managed to maintain itself in the market despite the competition represented by the European industry. © 2019 Verlag Vervuert. All rights reserved.